3-Acetoxy-fatty acid isoprenyl esters from androconia of the ithomiine butterfly Ithomia salapia - Mann, Florian; Szczerbowski, Daiane; de Silva, Lisa; McClure, Melanie; Elias, Marianne; Schulz, Stefan (Beilstein Journal of Organic Chemistry, 2020)
Male ithomiine butterflies (Nymphalidae: Danainae) have hairpencils on the forewings (i.e., androconia) that disseminate semiochemicals during courtship. While most ithomiines are known to contain derivatives of pyrrolizidine alkaloids, dihydropyrrolizines, or γ-lactones in these androconia, here we report on a new class of fatty acid esters identified in two subspecies, Ithomia salapia aquinia and I. s. derasa. The major components were identified as isoprenyl (3-methyl-3-butenyl) (Z)-3-acetoxy-11-octadecenoate, isoprenyl (Z)-3-acetoxy-13-octadecenoate (12) and isoprenyl 3-acetoxyoctadecanoate (11) by GC/MS and GC/IR analyses, microderivatizations, and synthesis of representative compounds. The absolute configuration of 12 was determined to be R. The two subspecies differed not only in the composition of the ester bouquet, but also in the composition of more volatile androconial constituents. While some individuals of I. s. aquinia contained ithomiolide A (3), a pyrrolizidine alkaloid derived γ-lactone, I. s. derasa carried the sesquiterpene α-elemol (8) in the androconia. These differences might be important for the reproductive isolation of the two subspecies, in line with previously reported low gene exchange between the two species in regions where they co-occur. Furthermore, the occurrence of positional isomers of unsaturated fatty acid derivatives indicates activity of two different desaturases within these butterflies, Δ9 and Δ11, which has not been reported before in male Lepidoptera.
Keywords: fatty acid esters; mass spectrometry; mimicry; pheromones; pyrrolizidine alkaloids

(untitled) - Chazot, N.; Willmott, K. R.; Lamas, G.; Freitas, A. V. L.; Piron‐Prunier, F.; Arias, C. F.; Mallet, J.; De‐Silva, D. L.; Elias, M. (Global Ecol. Biogeogr., 2019)

(untitled) - Beccaloni, G. W. (Trop. Lepid., 1997)

(untitled) - Müller, F. (Trans. Entomol. Soc. London, 1879)

(untitled) - Gauthier, J.; de Silva, D. L.; Gompert, Z.; Whibley, A.; Houssin, C.; Le Poul, Y.; McClure, M.; Lemaitre, C.; Legeai, F.; Mallet, J.; Elias, M. (Mol. Ecol., 2020)

(untitled) - Dasmahapatra, K. K.; Lamas, G.; Simpson, F.; Mallet, J. (Mol. Ecol., 2010)

(untitled) - McClure, M.; Mahrouche, L.; Houssin, C.; Monllor, M.; Le Poul, Y.; Frérot, B.; Furtos, A.; Elias, M. (J. Anim. Ecol., 2019)

(untitled) - Darragh, K.; Montejo-Kovacevich, G.; Kozak, K. M.; Morrison, C. R.; Figueiredo, C. M. E.; Ready, J. S.; Salazar, C.; Linares, M.; Byers, K. J. R. P.; Merrill, R. M.; McMillan, W. O.; Schulz, S.; et al. (Ecol. Evol., 2020)

(untitled) - González-Rojas, M. F.; Darragh, K.; Robles, J.; Linares, M.; Schulz, S.; McMillan, W. O.; Jiggins, C. D.; Pardo-Diaz, C.; Salazar, C. (Proc. R. Soc. B, 2020)

(untitled) - Boppré, M. (Naturwissenschaften, 1986)

(untitled) - Edgar, J. A.; Culvenor, C. C. J.; Pliske, T. E. (J. Chem. Ecol., 1976)

(untitled) - Schulz, S.; Beccaloni, G.; Brown, K. S., Jr; Boppré, M.; Freitas, A. V. L.; Ockenfels, P.; Trigo, J. R. (Biochem. Syst. Ecol., 2004)

(untitled) - Schulz, S. (Liebigs Ann. Chem., 1992)

(untitled) - Edgar, J. A. (Philos. Trans. R. Soc., B, 1975)

(untitled) - Schulz, S. (Eur. J. Org. Chem., 1998)

(untitled) - Honda, Y.; Honda, K.; Ômura, H. (J. Insect Physiol., 2006)

(untitled) - Schneider, D.; Boppré, M.; Zweig, J.; Horsley, S. B.; Bell, T. W.; Meinwald, J.; Hansen, K.; Diehl, E. W. (Science, 1982)

(untitled) - Culvenor, C. C. J.; Edgar, J. A. (Experientia, 1972)

(untitled) - Stamm, P.; Mann, F.; McClure, M.; Elias, M.; Schulz, S. (J. Chem. Ecol., 2019)

(untitled) - Schulz, S.; Francke, W.; Edgar, J.; Schneider, D. (Z. Naturforsch., C: J. Biosci., 1988)

(untitled) - Jones, R. V. H.; Sutherland, M. D. (Chem. Commun., 1968)

(untitled) - Kodama, M.; Yokoo, S.; Matsuki, Y.; Itô, S. (Tetrahedron Lett., 1979)

(untitled) - Baer, P.; Rabe, P.; Citron, C. A.; de Oliveira Mann, C. C.; Kaufmann, N.; Groll, M.; Dickschat, J. S. (ChemBioChem, 2014)

(untitled) - Ayasse, M.; Engels, W.; Hefetz, A.; Lübke, G.; Francke, W. (Z. Naturforsch., C: J. Biosci., 1990)

(untitled) - Duffield, R. M.; Fernandes, A.; Lamb, C.; Wheeler, J. W.; Eickwort, G. C. (J. Chem. Ecol., 1981)

(untitled) - Scribe, P.; Guezennec, J.; Dagaut, J.; Pepe, C.; Saliot, A. (Anal. Chem. (Washington, DC, U. S.), 1988)

(untitled) - Schulze, T.; Weldon, P. J.; Schulz, S. (Z. Naturforsch., C: J. Biosci., 2017)

(untitled) - Flachsbarth, B.; Fritzsche, M.; Weldon, P. J.; Schulz, S. (Chem. Biodiversity, 2009)

(untitled) - Ryhage, R.; Stenhagen, E. (Ark. Kemi, 1960)

(untitled) - Sémon, E.; Ferary, S.; Auger, J.; Le Quéré, J. L. (J. Am. Oil Chem. Soc., 1998)

(untitled) - Schlawis, C.; Schulz, S. (Nat. Prod. Rep., 2020)

(untitled) - More, J. D.; Finney, N. S. (Org. Lett., 2002)

(untitled) - Holmquist, C. R.; Roskamp, E. J. (J. Org. Chem., 1989)

(untitled) - Otera, J.; Yano, T.; Kawabata, A.; Nozaki, H. (Tetrahedron Lett., 1986)

(untitled) - Huang, G.; Hollingsworth, R. I. (Tetrahedron: Asymmetry, 1998)

(untitled) - König, W. A.; Gehrcke, B.; Pete, M. G.; Prestwich, G. D. (Tetrahedron: Asymmetry, 1993)

(untitled) - Neumann, A.; Patzelt, D.; Wagner-Döbler, I.; Schulz, S. (ChemBioChem, 2013)

(untitled) - Schulz, S.; Estrada, C.; Yildizhan, S.; Boppré, M.; Gilbert, L. E. (J. Chem. Ecol., 2008)

(untitled) - Yildizhan, S.; van Loon, J.; Sramkova, A.; Ayasse, M.; Arsene, C.; ten Broeke, C.; Schulz, S. (ChemBioChem, 2009)

(untitled) - Estrada, C.; Schulz, S.; Yildizhan, S.; Gilbert, L. E. (Evolution, 2011)

(untitled) - Wang, H.-L.; Brattström, O.; Brakefield, P. M.; Francke, W.; Löfstedt, C. (J. Chem. Ecol., 2014)

(untitled) - Bacquet, P. M. B.; Brattström, O.; Wang, H.-L.; Allen, C. E.; Löfstedt, C.; Brakefield, P. M.; Nieberding, C. M. (Proc. R. Soc. B, 2015)

The Chemistry of Pheromones and Other Semiochemicals I - Jurenka, R. (Insect pheromone biosynthesis, 2004)

(untitled) - Liénard, M. A.; Hagström, Å. K.; Lassance, J.-M.; Löfstedt, C. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Meinwald, J.; Meinwald, Y. C. (J. Am. Chem. Soc., 1966)

(untitled) - Mann, F.; Vanjari, S.; Rosser, N.; Mann, S.; Dasmahapatra, K. K.; Corbin, C.; Linares, M.; Pardo-Diaz, C.; Salazar, C.; Jiggins, C.; Schulz, S. (J. Chem. Ecol., 2017)

(untitled) - Murphy, B. T.; Cao, S.; Norris, A.; Miller, J. S.; Ratovoson, F.; Andriantsiferana, R.; Rasamison, V. E.; Kingston, D. G. I. (Planta Med., 2006)

(untitled) - Rossi, F. M.; Rojas, D.; Cervasio, D. A.; Posillico, J.; Parella, K.; Fitzgerald, T. D. (Chemoecology, 2020)